Social leaders and human rights defenders : a political-institutional perspective, 2019. (2021)
The article sought to answer the question: How do the homicide statistics between 2016 and 2019, and the prevention, protection and security measures of the Colombian state relate to social leaders and human rights defenders? By analysing in detail the INDEPAZ and government figures on homicides of leaders and human rights defenders by type of leadership and municipality, in the period 2016-2019 in Colombia. The research has an interpretative paradigm, with a qualitative approach; strengthened by descriptive and hermeneutic typologies, capable of linking subjects, objects and real phenomena, which is configured by different factors such as: illicit crops, drug trafficking routes, illegal and legal mining, forced displacement and the implementation of the Peace Agreement, by municipalities and even by types of leadership. Through the data and information provided, it was possible to conclude that there are irregularities in the state's prevention, protection and security measures.